Analysis of The Influence of Library Service Quality on User Satisfaction - Juanda Julianus; Nurlela Oematan (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
One of the main elements affecting patron happiness, particularly in educational settings, is the caliber of library services. For students, the library serves as an essential information source. The expectations of users and the actual services offered, however, frequently diverge. Prior research has demonstrated that high-quality services can boost students' enthusiasm for reading and their contentment with library resources. This study's methodology is quantitative and survey-based. The author selected 57 individuals from the population, all of whom were library patrons. Data collecting methods, including questionnaires and documentation, were employed to get the information required for this investigation. The data analysis's findings demonstrated that the library offered its patrons quite good services. The majority of respondents (22, or 38.6%) selected "Satisfied," indicating that they were happy with the facilities and services offered, particularly with regard to staff services and book collections. The lowest, "Not Satisfied," was reported by as many as two individuals, or 3.5%.